Review of the monograph “O. Yu. Dyagel. Analytical procedures of anticrisis management: monograph. Krasnoyarsk: Sibirial Federal University, 2020. 268 p.”. - D. V. Manushin; T. V. Kramin (Russian Journal of Economics and Law)
Objective: to conduct a detailed and complete analysis of a monograph by O. Yu. Dyagel2, which is devoted to the study of a wide range of issues related to analytical procedures of crisis management.Methods: the basic techniques of the abstract-logical method were used (analysis and synthesis, analogy, generalization, comparison, transition from abstract to concrete, etc.).Results: the leading line of this work is the differentiation of analytical procedures for crisis management, which implies a further standardization of individual diagnostics of enterprises’ financial condition. The reviewers emphasize the importance of the approaches to diagnosing the enterprises’ financial insolvency, systematized in the monograph.The reviewers assess the grouping of the author's approaches in the implementation of analytical procedures for crisis management, starting with preventive crisis management and ending with arbitration management.Scientific novelty: a new promising direction of financial analysis has been identified: standardization of an individual financial analysis based on specific groups of financial indicators suitable for a specific enterprise and its situation.Practical significance: the reviewers concluded that O. Yu. Dyagel’s monographic study contains examples of the practical application of the theoretical, methodological and regulatory approaches studied by the author, which significantly increases the possibility of their application in practice.